Analysis of Precast Concrete Construction Cost Comparison with Conventional Concrete in Building (Case Study of A1 & A2 Building) Sartikaasih Bhayangkara Hospital Bandung) - Wahidan, Fikri; Rahayu, Pony; Ramadhan, Erik Rizky; Farhan, Ohan (Indonesian Journal of Advanced Research, 2025)
This study discusses the comparison of cost and time efficiency between precast and conventional concrete systems in the structural work of building construction. The research adopts a quantitative comparative approach on two segments of the Sartikaasih Bhayangkara Hospital project in Bandung. The BoQ calculation results show that the precast system incurred lower total costs, amounting to IDR 17.6 billion (A1) and IDR 12.74 billion (A2), compared to the conventional system with IDR 19.86 billion (A1) and IDR 14.29 billion (A2). In terms of time, the precast system demonstrated significant efficiency, with savings of 65.02% on A1 and 21.43% on (A2). This efficiency contributes to the reduction of indirect costs and the risk of project delays. These findings indicate that the precast system can serve as a more economical and efficient alternative for building construction projects.